THE COMPARISON OF CYCLO]IE PERFORMANCE FOR DIFFERENT INLET GAS ATIIGtE - Novi Caroko, Suyitno (FT Univ Andalas, 2014)
This research goals to obtain cyclone engine designs that have high performance. Particle separation efficiency and pressure loss are two important parameters on cyclone performance. The cyclone that has a high efficiency with very low pressure loss required to reduce operating costs. The research was conducted by using CFD simulation (computational fluid dynamic). The cyclone has diameter 30 cm. Reynolds stress model (RSM) is used as a model in the turbulent CFD simulation. The inlet gas angle is varied from 0o, 15o, 30o, 45o, and 60o. For each inlet gas angle, the inlet gas velocity is varied by 13.6 m/s, 14.7 m/s, 16.3 m/s, and 17.8 m/s. During the CFD simulations, the particles were calculated using Euler-Lagrangian method. From this research can be concluded that the particle separation efficiency is higher than 90% for all inlet gas velocity variation. It is noted that the pressure drop is increasing linearly with velocity. The lowest pressure drop is found at inlet gas angle of 15o. For lower operating cost, the utilization of the inlet gas velocity 13.6 m/s and the inlet gas angle 15o is preferred. Wood gasification becomes more important recently because of . i Keywords : Cyclone, inlet gas angle, inlet gas velocity, CFD, and Reynolds Stress Turbulen RSM